Substantiation of projects that account for risk in the resource-saving technological changes at enterprises - Lesinskyi, Valentyn; Yemelyanov, Olexandr; Zarytska, Oksana; Symak, Anastasiya; Koleshchuk, Orest (Eastern-European Journal of Enterprise Technologies, 2018)
The purpose of the study was to model the investment risk of implementation of resource-saving technological changes at enterprises and to develop a method for consideration of risk for the substantiation of projects for introducing resource-saving technologies. Risk management is an important condition for increasing the expediency of technological change activities. In turn, the correct consideration of a risk factor can increase the confidence of owners of enterprises in the expediency of introduction of resource-saving technologies, which will increase the scale of such implementation. We determined principles, an information base, and a sequence of assessment of the potential of resource-saving technological changes at enterprises. We modeled an influence of prices for production resources, for which enterprises acquire industrial resources, on the effectiveness of resource-saving technologies implementation. The simulation results showed that the level of such efficiency is quite high only in a certain range of prices for resources. In this connection, we obtained expressions for determining the price ranges for a certain type of resource, which correspond to the three main options for the application of existing technological process. Such options are: to continue operation of the existing technology; to terminate its operation with the replacement of a new resource-saving technology; to stop using the existing technology without replacing it with a new one. The study substantiates expediency of consideration of a risk factor in substantiation of projects of resource-saving technological changes at enterprises by calculation of a value of the maximum acceptable amount of investments in such an introduction. It proposes to determine the maximum acceptable amount of investments based on a constructed set of scenarios of values of those project indicators that have a low level of predictability. There is no need to substantiate a value of a discount rate, which often has a high degree of subjectivity, for this approach to a risk factor. Application of the developed method of substantiation of projects for resource-saving technological changes will increase reasonableness of relevant investment decisions due to the comprehensive consideration of a risk factor in the practice of enterprises